In vitro Culture of Bovine Embryos in Murine ES Cell Conditioned Media Negatively Affects Expression of Pluripotency-Related Markers OCT4, SOX2 and SSEA1 - Oliveira, C. S. [UNESP]; de Souza, M. M. [UNESP]; Saraiva, N. Z. [UNESP]; Tetzner, T. A. D. [UNESP]; Lima, M. R. [UNESP]; Lopes, F. L. [UNESP]; Garcia, J. M. [UNESP] (Wiley-Blackwell, 2012)
Despite extensive efforts, establishment of bovine embryonic stem (ES) cell lines has not been successful. We hypothesized that culture conditions for in vitro-produced (IVP) embryos, the most used source of inner cell mass (ICM) to obtain ES cells, might affect their undifferentiated state. Therefore, the aim of this work was to improve pluripotency of IVP blastocysts to produce suitable ICM for further culturing. We tested KSR and foetal calf serum (FCS) supplements in SOF medium and ES cell conditioned medium (CM) on IVC (groups: KSR, KSR CM, FCS and FCS CM). Cleavage and blastocyst rates were similar between all groups. Also, embryonic quality, assessed by apoptosis rates (TUNEL assay), total cell number and ICM percentage did not differ between experimental groups. However, expression of pluripotency-related markers was affected. We detected down-regulation of OCT3/4, SOX2 and SSEA1 in ICM of FCS CM blastocysts (p < 0.05). SOX2 gene expression revealed lower levels (p < 0.05) on KSR CM blastocysts and a remarkable variation in SOX2 mRNA levels on FCS-supplemented blastocysts. In conclusion, pluripotency-related markers tend to decrease after supplementation with ES cell CM, suggesting different mechanisms regulating mouse and bovine pluripotency. KSR supplementation did not differ from FCS, but FCS replacement by KSR may produce blastocysts with stable SOX2 gene expression levels.